The Complex Essential Oils Highly Control the Toxigenic Fungal Microbiome and Major Mycotoxins During Storage of Maize - Wang, Limin; Liu, Bin; Jin, Jing; Ma, Longxue; Dai, Xiaofeng; Pan, Lin; Liu, Yang; Zhao, Yueju; Xing, Fuguo (Frontiers in Microbiology, 2019)
The contamination of maize with fungi and subsequent mycotoxins has been an important and long-standing safety problem in the maize industry. In this study, the inhibitory effects of the complex essential oils (cinnamaldehyde, citral, eugenol and menthol, 3:3:2:2, v/v) on fungal growth and mycotoxins production in stored maize were evaluated using traditional plate counting, internal transcribed spacer 2 (ITS2) sequencing and LC-MS/MS. Complex essential oils (0.02%) significantly (p<0.05) reduced the total fungi counts and the content of aflatoxin B1, zearalenone and deoxynivalenol in stored maize during 12 months of storage, and were more effective than propionic acid (0.2%). The fungal diversity of the control group was the highest with 113 operational taxonomic units (OTUs). During storage of maize kernels, Aspergillus, Fusarium, Wallemia, Sarocladium, and Penicillium were main genera. At 0-6 months, the fungal diversity was high and Fusarium was predominant genus. However, at 7-11 months, the fungal diversity was low and Aspergillus was predominant genus. During the later stages of storage, the prevalence of Aspergillus in maize treated with essential oils was significantly lower than (p<0.05) that observed in the propionic acid treated and control samples. The results of this study suggest that the complex essential oils may be employed successfully to control toxigenic fungi and subsequent contamination with mycotoxins in maize.